Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Inap di Rumah Sakit Kota Batu - Irbantoro, Dolly; Dewanto, Aryo; N, Asih Tri Rachmi (Jurnal Aplikasi Manajemen, 2015)
The growth of hospitals in Indonesia improve the competition between them. Thus, the hospitals are demanded to improve the services quality of the hospitals. The study aims to determine the influence of the perceived services quality variables into patient satisfaction of inpatient Hospitals in Batu. The design of study is cross sectional study with 110 respondent, as inpatient between April to May 2014 or their families in four hospitals in Batu. The samples were taken using purposive sampling technique. The variables of this research are Infrastructure, Personnel Quality, Clinical Care Process, Administrative Procedure, Patient Safety, Hospital Image, Hospital social responsibility, and Trusthworthiness of the hospital, as Independent variables. Patient satisfaction as dependent variables. The instrument of the research is questionnaires and measured with a scale of Likert 5 levels. The data were analyzed using multiple linear regression. The result showed that the Infrastructure, Personnel Quality, Clinical Care Process, Administrative Procedure, Patient Safety, Hospital Image, Hospital social responsibility, and Trusthworthiness of the hospital influence either partially or simultaneously to patient satisfaction. The dominant of independent variables is hospital image.